2021
DOI: 10.3389/fimmu.2021.660944
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Supports Differentiation of Terminally Exhausted CD8 T Cells

Abstract: Hypoxia, angiogenesis, and immunosuppression have been proposed to be interrelated events that fuel tumor progression and impair the clinical effectiveness of anti-tumor therapies. Here we present new mechanistic data highlighting the role of hypoxia in fine-tuning CD8 T cell exhaustion in vitro, in an attempt to reconcile seemingly opposite evidence regarding the impact of hypoxia on functional features of exhausted CD8 T cells. Focusing on the recently characterized terminally-differentiated and progenitor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 78 publications
(110 reference statements)
2
23
0
Order By: Relevance
“…Recently, exhausted T cells were further categorized into progenitor exhausted T cells and terminally exhausted T cells, as defined as PD1+TIM3-TCF1+ and PD1+TIM3+TCF1- T cells respectively [ 71 ]. Interestingly, it has been recently shown that hypoxia drove the differentiation of mouse progenitor exhausted T cells to terminally exhausted T cells in vitro [ 72 ]. While these two subsets of exhausted T cells await further characterization in HCC, another emerging question that merits further exploration is whether hypoxia drives exhausted T cell differentiation through HIF-mediated transcription of genes or hypoxia-induced metabolites in T cells.…”
Section: Hif-induced Metabolic Reprogramming Under Hypoxia and Drug Resistance In Hccmentioning
confidence: 99%
“…Recently, exhausted T cells were further categorized into progenitor exhausted T cells and terminally exhausted T cells, as defined as PD1+TIM3-TCF1+ and PD1+TIM3+TCF1- T cells respectively [ 71 ]. Interestingly, it has been recently shown that hypoxia drove the differentiation of mouse progenitor exhausted T cells to terminally exhausted T cells in vitro [ 72 ]. While these two subsets of exhausted T cells await further characterization in HCC, another emerging question that merits further exploration is whether hypoxia drives exhausted T cell differentiation through HIF-mediated transcription of genes or hypoxia-induced metabolites in T cells.…”
Section: Hif-induced Metabolic Reprogramming Under Hypoxia and Drug Resistance In Hccmentioning
confidence: 99%
“…Tumor-induced hypoxia is a major driving force that promotes angiogenesis and impairs effector immune responses [ 345 , 346 ]. Indeed, in vitro studies have demonstrated that hypoxia promotes the differentiation of PD-1+ Tim-3+ terminally exhausted-like CD8+ T cells [ 347 ]. Furthermore, these exhausted T cells are resistant to inhibitory checkpoints strategies [ 348 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an outcome of an in vitro study by Bannoud and colleagues. Terminally exhausted T cells due to representing a terminal differentiation position do not recover their effector functionality using ICIs ( 118 ).…”
Section: Factors Related To the Immaturity In Tumor Immune Ecosystemmentioning
confidence: 99%